INCIDENCE OF Echinococcucus granulosus IN OWNED DOGS IN LOKOJA METROPOLITAN, KOGI STATE. NIGERIA - Ngwamah, J. S.; Kayode, V. O.; Atawodi, J. C.; Dakum, Y. D.; Halima-Ohida, A.; Shitta, K. B. (FUDMA JOURNAL OF SCIENCES, 2025)
Echinococcosis is a zoonotic disease affecting both animals and human with significant health hazard and economic impacts. A study to evaluate the incidence of E. granulosus was carried out on dogs from six study sites in Lokoja, Kogi State.  Faecal samples from 300 dogs were collected and examined for the presence of E. granulosus cyst microscopically. A designed questionnaire was used to obtain both extrinsic and intrinsic information on the sampled dogs from their owners. Out of the 300 dog faecal samples screened, 59 had E. granulosus eggs with overall prevalence of 19.66%. Otokiti study unit had highest prevalence of 28.57%, GRA had the lowest prevalence (4.76%). With regards to sex, male and female dogs had a prevalence of 19.20% and 20.33% respectively. In terms of season, highest prevalence of 19.05% and lowest prevalence of 0.00% was recorded during rainy and dry season respectively. The incidence infection rate showed statistical significance with a (P< 0.05) relation to season. Free-range dogs recorded a prevalence of 22.69% while a prevalence of 8.06% was recorded in dogs reared under intensive condition (P< 0.05).  The result from this study revealed the presence of E.granulosus in the study area. Therefore, appropriate and regular deworming of dogs should be undertaken as well as awareness campaigns to educate the masses on the preventive measures is highly recommended to reduce risk of E. granulosus transmission to humans.
Keywords: Incidence; Echinococcus granulosus; Dogs; Nigeria